Some ectoparasitic trichodinids from Atlantic cod, Gadus morhua L., with a description of Trichodina cooperi n.sp. - Poynton, S. L.; Lom, J. (Canadian Journal of Zoology, 1989)
Trichodina murmanica Polyanskiy, 1955 (= Trichodina domerguei subsp. saintjohnsi Lom and Laird, 1969) and Trichodina cooperi n.sp. were commonly encountered on skin and fins of Atlantic cod, Gadus morhua L., near Halifax, Nova Scotia, Canada. A third species of Trichodina, probably new, was recorded from the skin of one fish. This is believed to be the first report of the genus Trichodina from the body surface of gadoid fish from eastern Canada, and the known geographic range of T. murmanica is extended. Trichodina cooperi n.sp. has an adoral ciliary spiral of 370–380° and is relatively large, the mean diameter of the body is 110 μm, of the adhesive disc (with dark center), 95 μm, and of the denticulate ring, 59 μm. The denticulate ring consists of 24–29 denticles (usually 27), with 7–9 radial pins per denticle. Each denticle has a broad blade, a large central part, and a slightly curved thorn of moderate to broad width, with a central rib when mature. The thorn is approximately twice the length of the blade. The horseshoe-shaped macronucleus has a diameter of 80.0 μm and the micronucleus is in the +y position. Trichodina spp. infected 26% of 39 wild fish 20 to < 60 cm long. Most wild fish yielded less than five ciliates per 24 × 50 mm smear.